Pituitary dysfunction with eosinophilic granulomatosis with polyangiitis presenting with diabetes insipidus: a case report and review of the literature - Zhang, Aifei; Liu, Xiaoxia; Wu, Pengjia; Qin, Longyan; Li, Na; Yin, Yi; Zeng, Jiashun (Frontiers in Immunology, 2025)
Central diabetes insipidus secondary to hypophysitis in eosinophilic granulomatosis with polyangiitis (EGPA) is very rare, and this article summarizes one case reported from our site as well as two previously reported patients with EGPA, both of whom had central diabetes insipidus, suggesting that new, rare organ involvement (pituitary gland) may occur in the early stages of EGPA or years later. The aim is to improve our understanding of central diabetes insipidus caused by EGPA involving the pituitary gland and avoid misdiagnosis or missed diagnosis.